Instagram Users' Experiences of Miscarriage. Issue 1 (January 2020) - Mercier, Rebecca J.; Senter, Katherine; Webster, Rachel; Henderson Riley, Amy
Abstract : OBJECTIVE: To explore the shared experiences of miscarriage using a qualitative analysis of social media posts on Instagram. METHODS: We performed this qualitative study by collecting text, photos, hashtags, and emoji from 200 Instagram posts on five arbitrarily selected days in 2019. Key eligibility criteria included posts that described a personal experience of miscarriage and that used the hashtag #ihadamiscarriage. Through directed content analysis, our multidisciplinary team conducted open coding to identify common topics in the data, developed a code book, and coded all posts. Twenty-five percent of posts were double-coded by two team members and analyzed for agreement. The codes were organized into overarching themes. RESULTS: Intercoder reliability was excellent (kappa 0.95). Themes included medical and physical experiences of miscarriage, social experiences of miscarriage, the emotional spectrum of experiencing a miscarriage, family identity and the effects of miscarriage, and mechanisms of processing and coping through a miscarriage. We observed complex and often conflicted emotional states and noted that the effects of miscarriage were felt for months and years by many Instagram users. Use of social media and disclosure of miscarriage was a source of coping for many users. CONCLUSION: Women post about their miscarriages on social media for a variety of reasons, especially to find support and community and to help break the silence around miscarriage. Health care providers may consider discussing use of this platform as a support and coping mechanism in the setting of pregnancy loss. Abstract : The social media platform Instagram provides insight into the personal experience of miscarriage and functions as a source of social support and coping for platform users.